The Influence of Employee Service Quality on Consumer Satisfaction at Syifamart As-syifa Boarding School Viewed from Sharia Economics - Fenny Damayanti Rusmana; Ade Albayan; Neng Rina (Lafadz Jaya Publisher, 2023)
The background of this research is that service quality is one of the company's assets in an effort to fulfill needs and desires and ultimately will create customer satisfaction. The purpose of this research is to determine the quality of employee service on customer satisfaction at Syifamart As-Syifa Boarding School from a sharia economic perspective. The method used in this research is quantitative. The results of this research show that Service quality has a positive and significant effect on customer satisfaction, the better the service provided, the more satisfied the customer will feel, because service quality is closely related to customer satisfaction, according to a simple definition as a condition where customer needs, desires and expectations can be met. All of this can be proven from the results of the hypothesis and also from the results of filling out the questionnaire from the respondents.